Hypovitaminosis D in post bariatric patients: Narrative review - Andrade, Isabella Pedrotti Leme de; Angelieri, Taís Donha Yarid; Cristóvão, Vitória de Oliveira; Teixeira, Luiza Santucci; Magalhães, Giovanna Rossetto; Marum, Carolina Vieira; Gentile, João Kleber de Almeida (Brazilian Journal of Case Reports, 2023)
Obesity can be associated with several diseases, signs, and symptoms. Among them, there is nutrient deficiency, especially vitamin D, which regulates calcium and phosphate and helps in bone remodeling. Vitamin D deficiency is related directly to the inadequate intake of foods rich in vitamins, less exposure to the sun and, mainly, to the sequestration of fat-soluble vitamins by the adipose tissue, making it even more difficult for the body to absorb them. Among these complications is the worsening of vitamin deficiency, with a focus on vitamin D, which is already present before the patient undergoes bariatric surgery. Regarding the types of bariatric surgery, each one establishes a degree of vitamin D deficiency that the patient will have postoperatively. That is, each type of bariatric surgery, as they are performed in different ways, directly interfere with the patient's absorption of vitamins. Postoperatively, vitamin D supplementation is recommended for all patients. However, due to poor patient compliance and lack of consent among physicians on the best form of supplementation, the deficiency is maintained, further impairing the treatment, and causing a worsening of the bariatric patient's condition.